2022
DOI: 10.3390/molecules27144491
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated Flavonoids in Topical Infections and Wound Healing

Abstract: The review presents prenylated flavonoids as potential therapeutic agents for the treatment of topical skin infections and wounds, as they can restore the balance in the wound microenvironment. A thorough two-stage search of scientific papers published between 2000 and 2022 was conducted, with independent assessment of results by two reviewers. The main criteria were an MIC (minimum inhibitory concentration) of up to 32 µg/mL, a microdilution/macrodilution broth method according to CLSI (Clinical and Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 260 publications
(344 reference statements)
0
20
0
Order By: Relevance
“…This makes it possible to inhibit enzymes associated with free radical formation, such as lipooxygenase, cyclooxygenase, and xanthine oxygenase. This is confirmed by Sychrová et al (2022) who showed that the presence of flavonoids in the diet may enhance the functioning of the antioxidant system, resulting in a reduction in MDA and LOOH, which are biomarkers of endogenous lipid peroxidation and radical-induced damage. Supported by exogenous antioxidants, the endogenous antioxidant system can compensate for excessive production of lipid peroxides and protect against the consequences of oxidative stress.…”
Section: Discussionmentioning
confidence: 64%
“…This makes it possible to inhibit enzymes associated with free radical formation, such as lipooxygenase, cyclooxygenase, and xanthine oxygenase. This is confirmed by Sychrová et al (2022) who showed that the presence of flavonoids in the diet may enhance the functioning of the antioxidant system, resulting in a reduction in MDA and LOOH, which are biomarkers of endogenous lipid peroxidation and radical-induced damage. Supported by exogenous antioxidants, the endogenous antioxidant system can compensate for excessive production of lipid peroxides and protect against the consequences of oxidative stress.…”
Section: Discussionmentioning
confidence: 64%
“…Some flavonoids comprise lipophilic chain or chains of varying lengths in their molecule. These prenylated flavonoids revealed a very good antibacterial effect against gram-positive and gram-negative bacteria [52]. Furthermore, the prenyl group can react with the adjacent OH groups to form a heterocyclic ring.…”
Section: S Sobrinusmentioning
confidence: 96%
“…Aloe vera [ 8 ], Calendula officinal [ 9 ], curcumin [ 10 ] and essential oils represent prominent examples with great contributions in one or more stages of the process of wound healing [ 1 , 11 ]. The efficacy of the different medicinal plants in wound healing could be related to the different classes of the secondary metabolites biosynthesised by medicinal plants, including triterpenoids, sterols (anti-inflammatory), flavonoids, polyphenolics (antioxidants), alkaloids (antimicrobial, anti-inflammatory) and/or essential oils (antimicrobial, anti-inflammatory) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%